Discovering our past : - Ashmore, Wendy (McGraw-Hill, 2006)
This brief, inexpensive introduction to the techniques, methods, and theoretical frameworks of contemporary archaeology follows the same organizing principle as the text Archaeology: Discovering Our Past but features less detail. Archaeological methods and theory are covered comprehensively--at a reasonable level of detail--in under 300 pages. Illustrative examples and case studies present a temporal and geographic balance of both Old and New World sites. Abundant student aids include maps of archaeological areas, extensive illustrations, chapter introductions and summaries, a guide to further reading at the end of each chapter, a glossary, a bibliography, and an index